Development and validation of a notational system to study the offensive process in football - Sarmento, H.; Anguera, T.; Campanico, J.; Leitao, J. (Medicina, 2010)
The most striking change within football development is the application of science to its problems and in particular the use of increasingly sophisticated technology that, supported by scientifi c data, allows us to establish a "code of reading" the reality of the game. Therefore, this study describes the process of the development and validation of an ad hoc system of categorization, which allows the different methods of offensive game in football and the interaction to be analyzed. Therefore, through an exploratory phase of the study, we identified 10 vertebrate criteria and the respective behaviors observed for each of these criteria. We heard a panel of five experts with the purpose of a content validation. The resulting instrument is characterized by a combination of fi eld formats and systems of categories. The reliability of the instrument was calculated by the intraobserver agreement, and values above 0.95 for all criteria were achieved. Two FC Barcelona games were coded and analyzed, which allowed the detection of various Tpatterns. The results show that the instrument serves the purpose for which it was developed and can provide important information for the understanding of game interaction in football.